2007
DOI: 10.1021/nl070530u
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoscrolls:  A Promising Material for Hydrogen Storage

Abstract: A multiscale theoretical approach was used for the investigation of hydrogen storage in the recently synthesized carbon nanoscrolls. First, ab initio calculations at the density functional level of theory (DFT) were performed in order to (a) calculate the binding energy of H2 molecules at the walls of nanoscrolls and (b) fit the parameters of the interatomic potential used in Monte Carlo simulations. Second, classical Monte Carlo simulations were performed for estimating the H2 storage capacity of "experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
224
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(233 citation statements)
references
References 27 publications
3
224
1
5
Order By: Relevance
“…Carbon based materials are candidates for such a purpose. Although several mechanisms of hydrogen storage through both physisorption and chemisorption have been proposed, [3][4][5][6][7] most of these efforts are far to reach the target of 6 wt% and immobilization hydrogen with binding strength of -0.2 ~ -0.4 eV/H 2 at ambient temperature and modest pressure for commercial applications specified by U.S. Department of Energy (DOE).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon based materials are candidates for such a purpose. Although several mechanisms of hydrogen storage through both physisorption and chemisorption have been proposed, [3][4][5][6][7] most of these efforts are far to reach the target of 6 wt% and immobilization hydrogen with binding strength of -0.2 ~ -0.4 eV/H 2 at ambient temperature and modest pressure for commercial applications specified by U.S. Department of Energy (DOE).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to single-walled carbon nanotubes where structural constraints on the electron wavefunctions make them either metallic or semiconducting, depending on their diameter and chirality 7 . Concurrent with unique electronic properties, the appropriate layer spacing of nanoscrolls might allow for energy storage applications 8,9 . Despite fascinating properties and a handful of theoretical studies of graphene nanoscrolls [10][11][12][13][14] , only few experimental studies [15][16][17][18] are reported for rGOx nanoscrolls.…”
mentioning
confidence: 99%
“…To date, however, no carbon host has been found to meet such stringent requirements. The feeble interaction between molecular hydrogen (H 2 ) and graphitic carbon is not likely to be sufficient for roomtemperature applications [3], yet recent work on carbon nanohorns [4,5] and nanoscrolls [6] report an appreciable enhancement of H 2 -CNM interactions solely via geometric confinement. In view of the above, the introduction of suitable dopants (particularly metals) into CNMs represents a viable way forward to enhance sorption energies.…”
mentioning
confidence: 99%
“…In view of the above, the introduction of suitable dopants (particularly metals) into CNMs represents a viable way forward to enhance sorption energies. Whereas abundant theoretical work exists to support these considerations [6,7], experiments probing H 2 binding in metal-doped CNMs are scarce. Careful experiments by Yang [8] have shown a 2% weight uptake by Li-doped nanotubes.…”
mentioning
confidence: 99%